Pengaruh Penerapan Maqomah terhadap Pengembangan Materi Pembelajaran Al-Qur'an dan Hadits di Madrasah Aliyah - Andi Saputra, Wahyu (Perkumpulan Peneliti dan Pegiat Literasi, 2024)
This study addresses the stagnation in the teaching methods of Al-Qur'an and Hadith at Madrasah Aliyyah Al-Falah Nagreg, emphasizing the need for innovation. The objective is to analyze the implementation of the Maqomah method, a systematic approach aimed at enhancing the learning materials of Al-Qur'an and Hadith. Utilizing a qualitative descriptive methodology, the research was conducted through literature reviews, classroom observations, interviews with teachers and students, and document analysis. The design follows a stepwise exploration of the Maqomah method's application and its impact on students’ comprehension. Key findings reveal that the Maqomah method significantly improves students' understanding and internalization of Islamic teachings, contributing to the overall quality of religious education. However, limitations such as time constraints and the specific context of Madrasah Aliyyah Al-Falah may influence the generalizability of the results. Future research should focus on broader applications of the method across different educational institutions and investigate its integration into national Islamic education curricula. The findings of this research provide valuable insights for educators seeking to innovate religious teaching methods in madrasahs and highlight the potential of Maqomah in fostering a deeper engagement with Islamic texts.